EU criminal justice and the challenges of diversity: legal cultures in the area of freedom, security and justice - Colson, Renaud; Field, Stewart (Cambridge University Press, 2016)
"EU Criminal Justice and the Challenges of Diversity examines how questions of cultural difference between Member States' legal traditions are being constructed, addressed and resolved in the development of the European Union's area of freedom, security and justice. The volume brings together leading socio-legal scholars and criminal justice professors from eight European countries and combines analytical approaches rooted in the social sciences with more normative approaches based on legal doctrine. It examines the construction of a common European criminal policy, explores some of the paths that may be followed by the EU in seeking to cope with national diversity in the field of criminal justice, and finally provides some insights into various forms of legal and cultural resistance offered by Member States to the European harmonization process. In the process it bridges disciplinary boundaries between law and social sciences and draws in a range of perspectives from around Europe"--